11 Let \( y=g(x) \) be the solution to the differential equation \( \frac{d y}{d x}=x y-2 \) with the initial condition \( g(2)=-1 \). What is the approximation for \( g(1) \) if Euler's method is used, starting at \( x=2 \) with two steps of equal size?
Real Tutor Solution
Answer
Solution
Reviewed and approved by the UpStudy tutoring team
Mind Expander
To apply Euler's method to approximate \( g(1) \), starting at \( x = 2 \) with two steps of equal size, we first determine the step size. We want to find \( g(1) \) and start from \( x=2 \) to \( x=1 \). The interval from \( 2 \) to \( 1 \) has a length of \( 1 \), so for two equal steps, the step size \( h \) is: \[ h = \frac{2 - 1}{2} = 0.5 \] Now we know that we will calculate approximations at \( x=2 \) and \( x=1.5 \), and then at \( x=1 \). 1. Starting point: \( g(2) = -1 \) 2. The derivative from the differential equation gives us \( \frac{dy}{dx} = xy - 2 \). At \( x = 2 \): \[ \frac{dy}{dx} = 2(-1) - 2 = -2 - 2 = -4 \] Using Euler's method to find \( g(1.5) \): \[ g(1.5) \approx g(2) + h \cdot \frac{dy}{dx} = -1 + 0.5 \cdot (-4) = -1 - 2 = -3 \] Now we use the new value \( g(1.5) = -3 \) to find \( g(1) \): 3. At \( x = 1.5 \): \[ \frac{dy}{dx} = 1.5(-3) - 2 = -4.5 - 2 = -6.5 \] Using this to calculate \( g(1) \): \[ g(1) \approx g(1.5) + h \cdot \frac{dy}{dx} = -3 + 0.5 \cdot (-6.5) = -3 - 3.25 = -6.25 \] Thus, the approximation for \( g(1) \) using Euler's method is \[ \boxed{-6.25} \]